ANALISIS TINGKAT AKURASI FSM DALAM PERAMALAN IPM INDONESIA MENGGUNAKAN GUI MATLAB - Vera Mandailina; Syaharuddin; Dewi Pramita; Sirajuddin (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2018)
This study aims to determine the best method in the forecasting system by creating a mathematical model of time series data in the form of Indonesia's Human Development Index (HDI) in 2010-2017. The methods tested are Moving Average (SMA, WMA and EMA), Exponential Smoothing Method (SES and DES), Naive Method, and Artificial Neural Network (Back Propagation). Then to see the level of accuracy based on MAD, MSE, and MAPE of each method. Determination of the best method in the forecasting system is very helpful in the process of forecasting data in the field which has implications for the government's decision system in making policies or decisions especially in the population, education, and people's economies. The best simulation method for predictions is the Exponential Smooting Holt Method with the predicted results of 2018 of 71.42 with the smallest MAD, MSE, and MAPE of 0.037; 0.001; and 0.053.